How to integrate recovery during heat acclimation - Ihsan, M.; Périard, J. D.; Racinais, S. (British Journal of Sports Medicine, 2020)
The games of the XXXII Olympiad have been announced from 23 July to 8 August 2021, coinciding with the height of the Japanese summer. Heat acclimation/acclimatisation (HA) is the most important countermeasure athletes can adopt to safeguard their health and performance when competing in the heat. However, it is important for practitioners to recognise that repeated daily exposures to heat stress is a physiologically demanding endeavour. Prolonged heat exposure is characterised by increased thermal and cardiovascular strain, augmented glycogen utilisation and fluid losses, increased hormonal responses (ie, increased cortisol and catecholamine secretion), cytokinaemia and endotoxaemia, which may result in sleep and gastrointestinal disturbances, augmented lethargy and delayed physical recovery.